Development of Family-Based Dietary Self-Management Support Program on Dietary Behaviors in Patients with Type 2 Diabetes Mellitus in Indonesia: A Literature Review - Aklima, Aklima; Kritpracha, Charuwan; Thaniwattananon, Ploenpit (Nurse Media Journal of Nursing, 2012)
Background: WHO statistics show that Indonesia has the fourth highest number of diabetes sufferers. The International Diabetes Federation‟s 5th estimated that in 2011 there were 71.4 million people in South East Asia region were suffering with DM Purpose: To develop a family-based dietary self-management support program to improve dietary behaviors in patients with T2DM. Method: A literature review was conducted by reviewing articles related evidence-based practices. Only articles in the English and Indonesian languages were reviewed. The search found eleven published experimental studies related to the topic. Result: Even though dietary self-management has benefits for patients with diabetes, many studies have found that these patients often have difficulty in establishing or maintaining an effective program to self-manage their dietary behaviors. Lack of family support is one factor that often seems to be related to such failures. Family participation in a diabetes education program also had positive psychosocial impacts. Otherwise, another study found that family might not always have a positive impact on self-management. Therefore, this review recommends that development of a family-based support program could be a positive factor in helping to improve dietary self-management behaviors in patients with T2DM. Self-management theory by Funnell and Anderson‟s work (2004) can guide the development of a program with the goal of empowering individuals and families in improving the patient‟s dietary behaviors. The program consists of: (1) reflecting on current and/or past self-management experiences by listening to the patient about their dietary behaviors, (2) discussing the emotions and feelings of the patients, (3) engaging the patient in improving their situation by active listening and helping the patient reflect on their problems and identifying effective strategies, (4) providing information about dietary management and problem-solving strategies, and (5) goal-setting and action planning by assisting the patient to write the goals and action plan on a specially prepared form. All of these sessions would involve the patient‟s family. Follow-up visits may be needed to evaluate the dietary behaviors of patients. Conclusion: The collaboration of patients, family and health care professionals can have a positive impact on the dietary self-management behaviors of patients with T2DM. Further study is needed, as there is a growing awareness of the important role in diabetes management of integrating family support into routine diabetes management. Key words: Type 2 diabetes mellitus, dietary behaviors, self-management, and family support.